GAMBARAN KUALITAS HIDUP ANAK PALSI SEREBRAL DI STELLA GD CENTER MEDAN TAHUN 2021 - SISCA SILVANA; VINCENSIUS KURNIAWAN ZAI; ADE PRYTA SIMAREMARE (JURNAL ILMIAH SIMANTEK, 2021)
Cerebral palsy is a chronic disability disease that often occurs in children, which has a very large impact and even affects thequality of life of children. Quality of life is an individual's perception of his life in terms of the cultural context, behavior andvalue system in which they live and is related to living standards, expectations, pleasures, and individual assessments oftheir position in life. This study aimed to describe the quality of life of children with cerebral palsy at Stella GrowthDevelopment Center Medan in 2021. This research is a descriptive study with a cross sectional design. Primary data wereobtained by questionnaires that had been previously validated from the results of interviews with respondents who met theinclusion and exclusion criteria and secondary data from patient medical record data. Of the 13 respondents, most of themwere female, 10 people (76.9%) were 5 and 8 years old with a total of 3 each. people (23.1%), all of the respondentsexperienced spastic cerebral palsy with the highest degree of gross motor function (GMFCS) experiencing grade 1,amounting to 6 people (46.2%). Patients with spastic cerebral palsy experience an increase in muscle tone so that themuscles experience stiffness and result in limited movement. The focus of the gross motor function classification is t oemphasize the child's abilities rather than limitations. The majority of children with cerebral palsy at the Stella GD CenterMedan in 2021 have a good quality of life.